National innovation systems a comparative analysis - Nelson, Richard R (New York Oxford University Press, 1993)
This study surveys the manner in which 17 different countries have evolved systems for technological innovation. Methods are compared not only in large, industrialized nations, but also in developing countries and smaller nations with high incomes.
Keywords: Technological innovations; Technology and state